Effectiveness of different substrate materials to prepare Trichoderma harzianum based bio-fungicides to control foot and root rot (Fusarium oxysporum) of tomato (Bangladesh Journal of Agricultural Research, 2015)
An investigation was undertaken to evaluate the effectiveness Trichoderma harzianum based bio-fungicides multiplied on different substrates. The substrates was rice bran, wheat bran, grass pea bran and their combinations with mustard oilcake (MOC) were used to mass culture T. harzianum for the management of foot and root rot disease of tomato seedling caused by Fusarium oxysporum in seedbed. All combinations of carrier materials were found effective for preparing T. harzianum based bio-fungicides to promote germination, seedling growth and reducing pre-emergence and post-emergence mortality of tomato seedling under F. oxysporum inoculated seedbed soils. The shoot length, shoot weight, root length and root weight of tomato seedling were enhanced significantly by the application of different substrate materials of T. harzianum based bio-fungicides under F. oxysporum inoculated seedbed conditions. The individual (rice bran, wheat bran, grass pea bran) and combination of substrates (rice bran + wheat bran, rice bran + mustard oilcake, rice bran + wheat bran + MOC and wheat bran + grass pea bran + MOC) were equally suitable for mass culturing of effective T. harzianum bio-fungicides for the management of foot and root rot disease of tomato seedling in seedbed condition.Bangladesh J. Agril. Res. 40(2): 279-289 June 2015